Re-Creation of the Character and Subjectivation in The Curious Incident of the Dog in the Night-Time - Mesut Günenç (Ideas: Journal of English Literary Studies)
This paper examines the creation of subject (the protagonist Christopher) and identity in Simon Stephens’ play The Curious Incident of the Dog in the Night-Time. The Curious Incident features vulnerability, dishonesty, different personalities, trust, experiences that go beyond the character’s bounds and relationships between subjects and identities. Christopher is incapable of understanding and knowing himself; as a result, Christopher must learn to rewrite his existence and life in order to reveal his individuality and uncover himself. In opposition to the idea of living inside the confines of universally accepted rules, the play offers a different and autonomous definition of subjectivity which deconstructs accepted rules. The subject tries to exist in a form of power that classifies the individual in society and stigmatises him/her with his/her own individuality. This study, focusing on Alain Badiou’s theory of subjectivation and within this context, his four terms (event, truth, body and present) in general and adding a fifth section as the event of daily life, argues that The Curious Incident of the Dog in the Night-Time depicts a collective subject similar to Badiou’s figure: a subject who rejects ordinary forms of communication for alternatives to authority and its structural inequalities.